IMPLEMENTASI PERATURAN DAERAH KABUPATEN KUANTAN SINGINGI NOMOR 10 TAHUN 2009 TENTANG PEMELIHARAAN KESEHATAN HEWAN (STUDI KASUS UPAYA PEMERINTAH DALAM PENANGGULANGAN HEWAN PENULAR RABIES) - Sari, Bella Etika; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Rabies disease is a contagious and zoonotic disease, it can infect humans through the bite of an animal infected with rabies. Rabies disease is caused by a zoonotic virus meaning rabies disease can be transmitted from animal to human, through the bite of Rabies (HPR). Kuantan Singingi Regency has a high population of rabid animals and wild animal rabies and many cases of bites caused by HPR. If not handled optimally the level of bite cases will increase. Therefore it is necessary to see the implementation of Regional Regulation number 10 of 2009 on Animal Health Maintenance. The theory used in this research is Policy Implementation. Especially the theory of Jan Merse to see the implementation of Regional Regulation number 10 of 2009 on Animal Health Maintenance related to government efforts in the prevention of rabies transmitting animals. This research uses qualitative descriptive method with triangulation technique, data collection with observation, interview and documentation. The result of the research is the implementation of the regulation of Kuantan Singingi Regency Number 10 Year 2009 on Animal Health Maintenance related to the efforts of the government in controlling rabies transmitters have been done but there are some that have not been done, among others: facilities, public participation is still lacking, and information obtained from it the factors that influence the implementation of the implementation of the Regulation of Kuantan Singingi Regency Number 10 Year 2009 on Animal Health Maintenance related to the government's efforts to control rabies transmitted animals include: limited funds, facilities, and low public and cultural awareness.Keywords: Rabies Disease, Animal Transmitting Rabies, Policy Implementation